Synthesis, docking, enzymatic and cellular assays of thieno[3,2-b]pyridine-thioether-1,3-diarylureas as VEGFR2 inhibitors - Queiroz, Maria João R.P. (2013)
Vascular endothelial growth factor receptor 2 (VEGFR2) is a class of tyrosine kinase receptors, expressed primarily in endothelial cells , and is activated by the specific binding of VEGF to the VEGFR2 extracellular regulatory domain, undergoing autophosphorylation, triggering signaling pathways leading to endothelial cell proliferation and subsequent angiogenesis.111 Small molecules may actas inhibitors by competing for the ATP-binding si te of the VEGFR2 intracellular tyrosine kinase domain, thereby preventing the intracellular signaling that leads to angiogenesisYl Herein, we report the synthesis of nove! nine 1-aryl-3-[2-, 3- or 4-(thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas as VEGFR2 inhibitors. The compounds presented below, with the arylurea in the meta position to the thioether, showed the lowest IC50 values (0.4-0.9 ]lM) in enzymatic assays. Using molecular docking (A) and molecular dynamics simulations, a convincing rationalization was achieved to explain the highest potency of these compounds.